2015
DOI: 10.1186/s12913-014-0659-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost to households in treating maternal complications in northern Ghana: a cross sectional study

Abstract: BackgroundThe cost of treating maternal complications has serious economic consequences to households and can hinder the utilization of maternal health care services at the health facilities. This study estimated the cost of maternal complications to women and their households in the Kassena-Nankana district of northern Ghana.MethodsWe carried out a cross-sectional study between February and April 2014 in the Kassena-Nankana district. Out of a total of 296 women who were referred to the hospital for maternal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 27 publications
5
49
3
Order By: Relevance
“…12 Pregnant women, particularly those with obstetric complications that require surgery and hospital admission, experience high health-care costs in countries without strong insurance systems, and will directly benefit from UHC. 1,6668 Countries that have adopted national health insurance programmes, such as Mexico and Rwanda, have reduced catastrophic health expenditures. 69,70 A study in Ethiopia found that the inclusion of free caesarean sections in an essential health intervention package averted 98 cases of poverty per $100 000 spent.…”
Section: Health-system Innovationsmentioning
confidence: 99%
“…12 Pregnant women, particularly those with obstetric complications that require surgery and hospital admission, experience high health-care costs in countries without strong insurance systems, and will directly benefit from UHC. 1,6668 Countries that have adopted national health insurance programmes, such as Mexico and Rwanda, have reduced catastrophic health expenditures. 69,70 A study in Ethiopia found that the inclusion of free caesarean sections in an essential health intervention package averted 98 cases of poverty per $100 000 spent.…”
Section: Health-system Innovationsmentioning
confidence: 99%
“…Similarly, some households in India were found to have made significant OOP payments for maternal health services, even though these services were meant to be free [ 24 ]. A previous study in the Kassena-Nankana municipality, Ghana, where this study was undertaken, revealed that cost of transport alone accounted for about 32% of the total expenditure incurred by families for the treatment of maternal complications during childbirth [ 25 ]. Thus, direct OOP payments in whichever form could still be a serious barrier to the use of health services [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal morbidity and mortality can endanger the survival and wellbeing of families [ 35 38 ]. Households in the study setting spend about 3% of their annual household expenditure on payments for maternal complications and face the risk of incurring catastrophic health expenditure[ 39 ]. Studies in other parts of Africa have reported that one maternal mortality reduces per capita GDP by US$0.36 per year [ 40 ].…”
Section: Discussionmentioning
confidence: 99%